Sovereign credit rating and resource-backed loans in African countries - (:unkn) unknown (My University, 2025)
During the past two decades, the number of African countries receiving a sovereign credit rating has increased exponentially compared to the previous period. In fact, faced with the drying up of conventional financing and the growing need for development finance, many African countries are turning to the eurobond market, which considers the sovereign credit rating as a credible signal of the sovereign's ability to pay their debt. At the same time, resource-rich African countries have resorted to resource-back loans from other developing nations -essentially China, whose principle is to use the natural resource endowments of the countries as collateral or payment in kind. Using the entropy balancing method, the purpose of this paper is to test whether African sovereigns resorting to resource-backed loans have on average a lower credit score compared to others. After performing a set of robustness checks, the study shows that the resource-backed loan has a negative and statistically significant impact on the sovereign credit rating for African countries.
Keywords: African Research